Design Analysis and Optimization of 6-DOF Coupling Parallel Mechanism based on Spiral Theory - Zenglin Ye; Hua Chen; Sa Sun (Jixie chuandong)
Aiming at the application of parallel mechanism in flexible assembly and polishing， a new 6-DOF coupling parallel mechanism is designed. The mechanism branch chain is designed based on the spiral theory， and the branch chain mechanism is optimized for the purpose of improving the rigidity of the mechanism and reducing the motion inertia. The coupled parallel mechanism is decoupled and analyzed according to the fixed principle， and the kinematics and equivalent motion of the mechanism are obtained. The number of degrees of freedom of the mechanism is verified by the modified G-K formula. Finally， a prototype of the coupled parallel mechanism is fabricated， and a motion control experiment is carried out. The experimental results show that the mechanism configuration is reasonable and practical.